Talent Management and the Financial Results of the Foreign Subsidiaries of Polish MNCs – Empirical Research Findings - Stor, Marzena; Haromszeki, Łukasz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2021)
Objective: To identify regularities between the overall advancement level of talent management and its constituent elements and company financial performance thanks to the significance of the human factor-based competitive advantage. Research Design & Methods: The research sample covered 200 nonfinancial Multinational Corportations (MNCs) headquartered in Poland with an overwhelming percentage share of Polish capital. They engage in a variety of economic activities. CATI and CAWI were used, as was a benchmarking measurement method was applied. The general description and analysis of the research data were done using descriptive and correlational statistics. Findings: The contributive significance of talent management to company’s performance falls between important and very important. The selected components of talent management exhibit positive and statistically significant internal relationships. This means that the higher the advancement levels of particular components of talent management, the higher its overall advancement level as an HRM subfunction. Moreover, the higher the overall advancement level of talent management, the better the company’s financial performance. This has led to the recognition that advancing the level of talent management results in better financial outcomes for companies. Implications / Recommendations: The research findings confirm that human capital, in its two basic categories, can be successfully treated as a company competitive factor. Skills, knowledge and competencies developed in talent management programmes may enhance company performance, including financial results, both at the HQs of MNCs and at foreign subsidiaries. Additionally, the results make it possible to formulate some practical recommendations that may support the managerial staff in making decisions regarding talent management, e.g. in planning the number and type of talent management components and ensuring their most optimal coexistence. Contribution: The research findings contribute to the development of management theory and practice, particularly to the development of talent management as a subfunction of HRM in MNCs. The authors have identified the regularities they theorised might exist between talent management and company financial performance due to the significance of human factor-based competitive advantage. Therefore, it can be assumed that research on the relationships between these variables in Polish MNCs helps fill in a research gap due to the object and subject of research.